2022
DOI: 10.3324/haematol.2021.280180
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-induced immune thrombotic thrombocytopenia: a possible pathogenic role of ChAdOx1 nCoV-19 vaccine-encoded soluble SARS-CoV-2 spike protein

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In this regard, we have found a marked increase of fibrinogen levels in the COVID-19 patient group compared to AIS patients without COVID-19, whereas D-dimer levels were similar in both groups. In comparison to VITT, in which the trigger of platelet activation may be the abnormal vaccine-induced sSP ( 13 ) and the maladaptive immunity plays a fundamental role in pathogenesis ( 24 ), and in comparison to critically ill COVID-19 patients, where platelets are significantly altered to a more active phenotype and this activation is modulated by immune complexes ( 25 ), in COVID-19 related-AIS, sSP and immune complexes seems to have a secondary role. In fact, although we did not have the opportunity to study in vivo the platelets of the AIS patient of our cohort, in our experiments we observed a similar pattern of HDs' platelet activation after incubation with sera from AIS with and without COVID-19 patients and, moreover, neither SP antibody nor anti-FcγRIIa monoclonal antibody inhibited this activation suggesting a minor role of sSP and immune-mediated mechanisms in this subset of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we have found a marked increase of fibrinogen levels in the COVID-19 patient group compared to AIS patients without COVID-19, whereas D-dimer levels were similar in both groups. In comparison to VITT, in which the trigger of platelet activation may be the abnormal vaccine-induced sSP ( 13 ) and the maladaptive immunity plays a fundamental role in pathogenesis ( 24 ), and in comparison to critically ill COVID-19 patients, where platelets are significantly altered to a more active phenotype and this activation is modulated by immune complexes ( 25 ), in COVID-19 related-AIS, sSP and immune complexes seems to have a secondary role. In fact, although we did not have the opportunity to study in vivo the platelets of the AIS patient of our cohort, in our experiments we observed a similar pattern of HDs' platelet activation after incubation with sera from AIS with and without COVID-19 patients and, moreover, neither SP antibody nor anti-FcγRIIa monoclonal antibody inhibited this activation suggesting a minor role of sSP and immune-mediated mechanisms in this subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the antibodies against platelet factor-4 (PF4) which are the hallmark of VITT, are only sporadically found in COVID-19 patients, and in most cases, they are functionally inactive (12). A role of SP in VITT-and COVID-19-related discoagulopathy has been advocated by our group and others (13,14). Based on all this data, we aimed to analyze the clinical/radiological characteristics, endothelial dysfunction and coagulation biomarkers of a cohort of AIS patients affected by COVID-19 in comparison with a cohort of AIS patients without COVID-19 and to verify whether, similarly to VITT, SP could play a pathogenic role in platelet activation in AIS patients with COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sSP was detected in serum of 3 VITT patients and within a cerebral arterial thrombus from one of them where it co-localized with platelets. Moreover, platelet activation induced in vitro by VITT serum was partially inhibited by an antibody against sSP (54). Based on these findings a multiple hit model was proposed identifying three steps (Figure 1D): the first is the activation of platelets and endothelial cells by soluble spike, then This article is protected by copyright.…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“…74 De Michele et al have shown in a small case series that soluble spike protein in VITT serum induces the activation of healthy donor platelets as measured by integrin α IIb β 3 activation, with serum-induced activation significantly reduced by the addition of an antibody against the S1 subunit of the spike protein. 75 Furthermore, published abstracts from two different groups implicate endothelial activation as a potential additional or even alternative driver to platelet activation for thrombus formation in VITT. 76 77 Interestingly, sera from patients that fit the clinical syndrome in which PF4 antibodies are not detectable appear to demonstrate endothelial-associated ex vivo thrombus formation.…”
Section: Mechanisms Of Thrombosismentioning
confidence: 99%